Timeless investigations: cases of disappearance (Rivista di Psicopatologia Forense, Medicina Legale, Criminologia, 2021)
The work intends to show the complexity of cold cases, unresolved and closed cases that could again be the subject of an investigative procedure thanks to novelties such as testimonies or evidence. In particular, it focuses on cases of disappearance of people, national and international, on the difficulty of research and investigations and the treatment of the psychological aspects that this phenomenon can cause. Analyzing the cases of disappearance of Emanuela Orlandi and Denise Pipitone, we note how the investigative inconsistencies did not lead to the resolution of the case and the time that passed made everything more difficult.